Electrically conductive fibers in cluster bomblets which targeted the electric power system of FR Yugoslavia in 1999 - Anđelković-Lukić, Mirjana; Stojanović, Mirjana (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: The paper presents the mode of operation of the CBU-102(V) 2/B cluster bomb, weighing about 340 kg and containing bomblets with electrically conductive fibers for disabling power plants.Methods: Physical and chemical analyses of the fibers were performed. The following test methods were used for fiber characterization: a binocular microscope for determining fiber thickness and a qualitative XRF analysis performed on an XRF-MiniPal spectrometer, PANalytical. The XRFanalysis aimed at qualitative detection of the present elements, which was confirmed by a quantitative chemical analysis.Results: The semi-quantitative XRF analysis determined the content of gallium (0.007%), the peak of which was detected on the spectrum. Gallium nitride is a material that can be used as a semiconductor. The chemical analysis was performed on an atomic absorption spectrophotometer Analyst 300, Perkin Elmer.Conclusion: The instrument for differential thermal analysis and thermogravimetry (DTA/TG), NETZCH STA 409 EP (operational range from 20°C to 1000°C), confirmed that the sample was of 50% silicate origin, non-toxic and with heavy metal content in traces. The rest of the sample is aluminum whose presence in soil can cause decline in soil fertility thus leading to decline in crop yields.
Keywords: cluster bomb; electrically conductive fibers; energy system; chemical analysis; thermochemical analysis; silicate; aluminum; environmental impact; soil; declined fertility; reduced yield; chemical warfare